Skeletal muscle cell protein dysregulation highlights the pathogenesis mechanism of myopathy-associated p97/VCP R155H mutations - Anna Luzzi; Feng Wang; Shan Li; Michelina Iacovino; Michelina Iacovino; Tsui-Fen Chou; Tsui-Fen Chou (Frontiers in Neurology, 2023)
p97/VCP, a hexametric member of the AAA-ATPase superfamily, has been associated with a wide range of cellular protein pathways, such as proteasomal degradation, the unfolding of polyubiquitinated proteins, and autophagosome maturation. Autosomal dominant p97/VCP mutations cause a rare hereditary multisystem disorder called IBMPFD/ALS (Inclusion Body Myopathy with Paget’s Disease and Frontotemporal Dementia/Amyotrophic Lateral Sclerosis), characterized by progressive weakness and subsequent atrophy of skeletal muscles, and impacting bones and brains, such as Parkinson’s disease, Lewy body disease, Huntington’s disease, and amyotrophic lateral ALS. Among all disease-causing mutations, Arginine 155 to Histidine (R155H/+) was reported to be the most common one, affecting over 50% of IBMPFD patients, resulting in disabling muscle weakness, which might eventually be life-threatening due to cardiac and respiratory muscle involvement. Induced pluripotent stem cells (iPSCs) offer an unlimited resource of cells to study pathology’s underlying molecular mechanism, perform drug screening, and investigate regeneration. Using R155H/+ patients’ fibroblasts, we generated IPS cells and corrected the mutation (Histidine to Arginine, H155R) to generate isogenic control cells before differentiating them into myotubes. The further proteomic analysis allowed us to identify differentially expressed proteins associated with the R155H mutation. Our results showed that R155H/+ cells were associated with dysregulated expression of several proteins involved in skeletal muscle function, cytoskeleton organization, cell signaling, intracellular organelles organization and function, cell junction, and cell adhesion. Our findings provide molecular evidence of dysfunctional protein expression in R155H/+ myotubes and offer new therapeutic targets for treating IBMPFD/ALS.